HEMOPHILIC MENINGITIS IN CHILDREN - T. V. Egorova; L. V. Malkova; I. F. Dziuban; A. L. Stolbov (LLC "Diagnostics and Vaccines", 2015)
Bacterial purulent meningitis (BPM) was detected and treated in 63children aged from 1 month till 17 years during 2006-2010. 63,5% (40 patients) of patients were children of first three years old. In this group etiological distribution of the children was as follows: 55% were meningococcal, 17,5% were hemophilic, 2,5% were esherichiosic, 2,5% were staphylococcal, 22,5% were of unclear etiology. The peculiarities of clinics, causes and treatment of Hib - meningitis were explored in 7 children. The criteria were found which indicate the possibility of prolonged wave-like course of Hib-meningitis in the acute period of the disease.